Characterization of Prunus Necrotic Ringspot Virus and Cherry Virus A Infecting Myrobalan Rootstock - Ben Mansour, Karima; Komínek, Petr; Komínková, Marcela; Brožová, Jana (Viruses, 2023)
Prunus necrotic ringspot virus (PNRSV) and cherry virus A (CVA) are two viruses that mainly infect plants of the genus Prunus. Full-length sequences of these two viruses, collected in the Czech Republic from Prunus cerasifera plants, were obtained via HTS sequencing. Phylogenetic analyses based on the NJ method and Splitstree tools showed that the Czech PNRSV isolate (ON088600-ON088602) is a divergent isolate from other molecular groups, sharing less than 97% pairwise nucleotide identity with members of other groups. The Czech CVA isolate (ON088603) belonged to molecular subgroup III-2, clustered with isolates from non-cherry hosts, and shared the highest pairwise nucleotide identity (99.7%) with an isolate of Australian origin.
Keywords: symptoms; Flexiviridae; PNRSV; Terminalia; Ilarvirus; Phylogeny; Austrálie; biological assay; fylogeneze; nukleotidy; Australia; CVA; phylogenetic analysis; Nucleotides